Is Computer-based Communication A Valuable Addition to Victim-offender Mediation? A Qualitative Exploration among Victims, Offenders and Mediators - Bonensteffen, Florian (Victims & offenders, 2022)
Computer-based communication (CBC) has become an inevitable aspect of our communication infrastructure and a lasting alternative to face-to-face conversations. Yet, CBC (e.g. video conferencing) is not common practice for victim-offender mediation (VOM). Based on eighteen semi-structured interviews with adult victims, offenders and mediators, we provide a heuristic assessment of CBC applicability in VOM. Interviewees associated CBC with higher environmental safety compared to face-to-face mediation, and with richer emotional information compared to indirect VOM (e.g., letter exchange). Risks comprised technical and privacy concerns. Our findings provide insight into stakeholder perceptions of the usability of CBC-VOM and thus directions for effective employment.